The nature of things - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Diversity not Adversity: Sustaining Livelihoods with Biodiversity By I Koziell, IIED Biodiversity and Livelihoods Group, 2001. 58 pp. ISBN 1 899 825 68 1 US$ 30 Euro 34 ( Stock number: 7822IIED)